2010
DOI: 10.2135/cropsci2010.04.0195
|View full text |Cite
|
Sign up to set email alerts
|

MlAB10: A Triticum turgidum Subsp. dicoccoides Derived Powdery Mildew Resistance Gene Identified in Common Wheat

Abstract: Powdery mildew is an economically important disease in wheat (Triticum aestivum L.). NC97BGTAB10 contains powdery mildew resistance introgressed from wild emmer wheat (T. turgidum subsp. dicoccoides). The objectives of this research were to genetically characterize the powdery mildew resistance in NC97BGTAB10, identify SSR markers closely linked to the resistance gene, and provide evidence that the gene is novel. One hundred thirty nine F2:3 lines from the cross NC97BGTAB10/Saluda were evaluated in the field a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…** Region of significant association without extension based on LD decay. (1) Yahiaoui et al 2004 , (2) Singh et al 2018 , (3) Shi et al 1998 , (4) Peusha et al 2004 , (5) Lillemo et al 2008 , (6) Wan et al 2020 , (7) Zhu et al 2005 , (8) Zhan et al 2014 , (9) Wu et al 2019 , (10) Dong et al 2020 , (11) Zhang et al 2018 , (12) Tan et al 2019 , (13) Zhang et al 2019 , (14) Wang et al 2021 , (15) Wu et al 2022 , (16) Li et al 2020a , b , (17) Zhu et al 2006 , (18) Mu et al 2022 , (19) Maxwell et al 2010 , (20) Mohler et al 2005 , (21) Zhang et al 2023 , (22) Li et al 2020a , (23) Xu et al 2010 , (24) Blanco et al 2008 , (25) Petersen et al 2015 , (26) Xue et al 2012 , (27) Zhang et al 2010 , (28) Sánchez-Martín et al 2016 , (29) Gao et al 2012 , (30) Zhang et al 2016 , (31) Hewitt et al 2021 , (32) McIntosh et al 2013 , (33) Perugini et al 2008 , (34) Tan et al 2018 , (35) Zou et al 2018 , (36) Ben-David et al 2010 , (37) Ji et al 2008 , (38) Yao et al 2007 , (39) Singrün et al 2004 , (40) Worthington et al 2014 , (41) Qiu et al 2005 , (42) Chhuneja et al 2015 , (43) Ouyang et al 2014 , (44) Han et al 2009 , (45) Luo et al 2009 , (46) Xiao et al 2013 , (47) Huang et al 2002 , (48) Lutz et al 1995 , (49) Zeller et al ...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…** Region of significant association without extension based on LD decay. (1) Yahiaoui et al 2004 , (2) Singh et al 2018 , (3) Shi et al 1998 , (4) Peusha et al 2004 , (5) Lillemo et al 2008 , (6) Wan et al 2020 , (7) Zhu et al 2005 , (8) Zhan et al 2014 , (9) Wu et al 2019 , (10) Dong et al 2020 , (11) Zhang et al 2018 , (12) Tan et al 2019 , (13) Zhang et al 2019 , (14) Wang et al 2021 , (15) Wu et al 2022 , (16) Li et al 2020a , b , (17) Zhu et al 2006 , (18) Mu et al 2022 , (19) Maxwell et al 2010 , (20) Mohler et al 2005 , (21) Zhang et al 2023 , (22) Li et al 2020a , (23) Xu et al 2010 , (24) Blanco et al 2008 , (25) Petersen et al 2015 , (26) Xue et al 2012 , (27) Zhang et al 2010 , (28) Sánchez-Martín et al 2016 , (29) Gao et al 2012 , (30) Zhang et al 2016 , (31) Hewitt et al 2021 , (32) McIntosh et al 2013 , (33) Perugini et al 2008 , (34) Tan et al 2018 , (35) Zou et al 2018 , (36) Ben-David et al 2010 , (37) Ji et al 2008 , (38) Yao et al 2007 , (39) Singrün et al 2004 , (40) Worthington et al 2014 , (41) Qiu et al 2005 , (42) Chhuneja et al 2015 , (43) Ouyang et al 2014 , (44) Han et al 2009 , (45) Luo et al 2009 , (46) Xiao et al 2013 , (47) Huang et al 2002 , (48) Lutz et al 1995 , (49) Zeller et al ...…”
Section: Resultsmentioning
confidence: 99%
“…Pm genes described in an overlapping genomic interval with the GWAS peak are highlighted in bold. (1) Shi et al 1998 , (2) Peusha et al 2004 , (3) Lillemo et al 2008 , (4) Tosa et al 1987 , (5) Sánchez-Martín et al 2021 , (6) Mohler et al 2013 , (7) Li et al 2019 , (8) Fu et al 2013 , (9) Komáromi et al 2016 , (10) Yu et al 2018 , (11) Xu et al 2011 , (12) Niu et al 2008 , (13) Hu et al 2008 , (14) Sun et al 2022 , (15) Wan et al 2020 , (16) Zhu et al 2005 , (17) Zhan et al 2014 , (18) Wu et al 2019 , (19) Dong et al 2020 , (20) Zhang et al 2018 , (21) Tan et al 2019 , (22) Zhang et al 2019 , (23) Wang et al 2021 , (24) Wu et al 2022 , (25) Li et al 2020a , b , (26) Zhu et al 2006 , (27) Mu et al 2022 , (28) Maxwell et al 2010 , (29) Mohler et al 2005 , (30) Zhang et al 2023 , (31) Driscoll and Bielig 1968 , (32) McIntosh et al 2013 , (33) Chao et al 2019 , (34) Xu et al 2008 , (35) Blanco et al 2008 ,(36) Petersen et al 2015 , (37) Xue et al 2012 , (38) Zhang et al 2010 , (39) Sánchez-Martín et al 2016 , (40) Gao et al 2012 , (41) Zhang et al 2016 , (42) He et al 2018 , (43) Xing et al 2018 , (44) Hao et al 2018 , (45) Hewitt et al 2021 , (46) McIntosh et al 2013 , (47) Perugini et al 2008 , (48) Tan et al 2018 , (49) Zou et al…”
Section: Resultsmentioning
confidence: 99%
“…Eleven Pm genes have been reported to be located on chromosome arm 2BL from various gene donors, including Pm6 from Triticum timopheevii (Wan et al, 2020), Pm33 from T. persicum Vav. (Zhu et al, 2005), Pm51 from a Thinopyrum ponticum introgression line (Zhan et al, 2014), Pm52 from Chinese wheat cultivar Liangxing 99 (Wu et al, 2019), Pm63 from Iranian wheat landrace PI 628024 (Tan et al, 2019), Pm64 from wild emmer (Zhang et al, 2019), PmQ from Chinese wheat landrace Qingxinmai (Li H. H. et al, 2020), MlZec1 and MlAB10 both from T. dicoccoides (Mohler et al, 2005;Maxwell et al, 2010), PmKN0816 from the Chinese wheat breeding line KN0816 (Wang et al, 2021) and PmLS5082 from the Chinese wheat breeding line LS5082 (Wu et al, 2019), suggesting chromosome arm 2BL is a potential R gene-rich region and complex molecular modules and mechanisms may be involved in the chromosome arm 2BL. T. timopheevii derived Pm6 was the first Pm gene identified on chromosome 2BL and was transferred into the wheat genetic background in the form of wheat-T. timopheevii 2B/2G introgression lines (Jorgensen and Jensen, 1973;Bennett, 1984;Ji et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Then, using molecular markers derived from the BSR-Seq, it was further located at an interval of 4.2 cM corresponding with the 647.1-656.0 Mb physical interval based on the reference genome of Chinese Spring. Prior to PmYD588 , ten Pm genes, namely, Pm6 ( Wan et al, 2020 ), Pm33 ( Zhu et al, 2005 ), Pm51 ( Zhan et al, 2014 ), Pm52 ( Wu et al, 2019 ), Pm63 ( Tan et al, 2019 ), Pm64 ( Zhang et al, 2019 ), PmQ ( Li Y. et al, 2020 ), PmKN0816 ( Wang et al, 2021 ), MlZec1 ( Mohler et al, 2005 ), and MlAB10 ( Maxwell et al, 2010 ) have previously been reported on the chromosome arm 2BL. However, PmYD588 can be distinguished from Pm6 (698.3–699.2 Mb), Pm33 (779.1–784.3 Mb), Pm51 (709.8–739.4 Mb), Pm52 (581.0–585.0 Mb), Pm63 (710.3–723.4 Mb), Pm64 (699.2–705.5 Mb), PmQ (710.7–715.0 Mb), PmKN0816 (700.4–710.3 Mb), MlZec1 (796.7–780.0 Mb), and MlAB10 (796.7–780.0 Mb) in its physical interval, suggesting PmYD588 is most likely a new Pm gene.…”
Section: Discussionmentioning
confidence: 99%